(untitled) (Journal of Eye Movement Research, 2010)
The idea of gaze guidance is to lead a viewer’s gaze through a visual display in order to facilitate the viewer’s search for specific information in a least-obtrusive manner. This study investigates saccadic orienting when a viewer is guided in a fast-paced, low-contrast letter identification task. Despite the task’s difficulty and although guiding cues were ad-justed to gaze eccentricity, observers preferred attentional over saccadic shifts to obtain a letter identification judgment; and if a saccade was carried out its saccadic constant error was 50%. From those results we derive a number of design recommendations for the process of gaze guidance.